IMPLEMENTASI LOGIKA FUZZY MAMDANI PADA PENGENDALIAN NUTRISI TANAMAN HIDROPONIK - Adita Aulia A. Rachman; Fakhriy Hario Partiansyah; Gaguk Asmungi (Jurnal Mahasiswa TEUB, 2023)
The increasing demand for vegetables as a consumption commodity and the decreasing availability of land for conventional cultivation have led to hydroponic cultivation as one of the solutions. Unlike soil-based farming, hydroponics uses water as the medium for growing. However, the nutrient levels of hydroponic plants must be maintained within a certain range. Nutrient deficiencies can cause leaves to wilt and curl, while excess nutrients can cause leaves to turn dark green, indicating poor plant health. Thus, the purpose of this research is to develop an automatic nutrient controller that operates according to a setpoint to ensure that hydroponic plants receive the appropriate nutrients. In this study, Mamdani fuzzy logic control is used because of its simple structure, and its linguistic methods can be analyzed mathematically, making it easy to understand. Fuzzy logic control converts crisp input values into fuzzy values using membership functions, then applies the rules that have been created based on implication, followed by rule composition, and finally defuzzification to convert the fuzzy values into crisp output values. Index Terms— Hydroponics, Mamdani Fuzzy Logic Control, Membership Function DAFTAR PUSTAKA[1] Badan Pusat Statistik. 2020. Produksi Tanaman Sayuran 2017-2020. Statistik Telekomunikasi Indonesia. Jakarta.[2] Hudoro. 2003. Keuntungan Budidaya Hidroponik. Rineka Cipta: Jakarta.[3] Mashumah, Siti, dkk. 2018. Nutrient Film Technique based Hydroponic System Using Fuzzy Logic Control. International Seminar on Intelligent Technology and Its Applications (ISITIA). Institut Teknologi Sepuluh Nopember.[4] Triwidyastuti, Y., Puspasari, I., & Harianto, H. 2018. Comparison between PID and Fuzzy Controller to Hydroponi Temperature. International Conference on Information Technology Applications and Systems (ICITAS).[5] Safura, S. A. El, dkk. 2018. Rancang Bangun Sistem Kontrol Logika Fuzzy Pada Pengaturan Nutrient Film Technique. e-Proceeding of Engineering, 5(1), 959-966.